이온질화된 공구강 표면의 산화 및 공식거동 - 최한철(Han-Cheol Choe); 이호종(Ho-Jong Lee); 정용운(Yong-Woon Jeong) (Biuletyn Uniejowski, 2005)
SKD 11 steel has been widely used for tools, metallic mold and die for press working because of its favorable mechanical properties such as high toughness and creep strength as well as excellent oxidation resistance. The ion nitrided tool steel containing Mo results in improvement of corrosion resistance, strength at high temperature and pitting resistance, especially in $Cl^-$ contained environment. But the Mo addition causes a disadvantage such as lower oxidation resistance at elevated temperature. In this study, several effects of ion-disadvantage on the oxidation characteristics for SKD 11 steel with various oxidation temperature were investigated. SKD 11 steels were manufactured by using vacuum furnace and solutionized for 1 hr at $1,050^{°}C$. Steel surface was ion nitrided at $500^{°}C$ for 1 hr and 5 hr by ion nitriding equipment. ion nitrided specimen were investigated by SEM, OM and hardness tester. Oxidation was carried out by using muffle furnace in air at $500^{°}C,\;700^{°}C\;and\;900^{°}C$ for 1hr, respectively. Oxidation behavior of the ion nitrided specimen was investigated by SEM, EDX and surface roughness tester. The conclusions of this study are as follows: It was found that plasma nitriding for 5 hr at $500^{°}C$, compared with ion nitriding for 1 hr at $500^{°}C$, had a thick nitrided layer and produced a layer with good wear, corrosion resistance and hardness as nitriding time increased. Nitrided SKD 11 alloy for 1hr showed that wear resistance and hardness decreased, whereas surface roughness increased, compared with nitrided SKD 11 alloy for 5 hr. The oxidation surface at $900^{°}C$ showed a good corrosion resistance.